16p11.2 deletion in patients with paroxysmal kinesigenic dyskinesia but without intellectual disability. Issue 11 (11th October 2018) - Li, Wen; Wang, Yifan; Li, Bin; Tang, Bin; Sun, Hui; Lai, Jinxing; He, Na; Li, Bingmei; Meng, Heng; Liao, Weiping; Liu, Xiaorong
Abstract: Introduction: Mutations of the PRRT2 gene are the most common cause for paroxysmal kinesigenic dyskinesia. However, patients with negative PRRT2 mutations are not rare. The aim of this study is to determine whether copy number variant of PRRT2 gene is another potential pathogenic mechanism in the patients with paroxysmal kinesigenic dyskinesia with negative PRRT2 point and frameshift mutations. Methods: We screened PRRT2 copy number variants using the AccuCopy™ method in 29 patients with paroxysmal kinesigenic dyskinesia with negative PRRT2 point and frameshift mutations. Next‐generation sequencing was used to determine the chromosomal deletion sites in patients with PRRT2 copy number variants, and to exclude mutations in other known causative genes for paroxysmal kinesigenic dyskinesia. Results: Two sporadic patients with negative PRRT2 point and frameshift mutations (6.9%) were identified to have de novo PRRT2 copy number deletions (591 and 832 Kb deletions located in 16p11.2). The two patients presented with pure paroxysmal kinesigenic dyskinesia and paroxysmal kinesigenic dyskinesia and benign infantile convulsions, respectively. They had normal intelligence and neuropsychiatric development, in contrast to those previously reported with 16p11.2 deletions complicated with neuropsychiatric disorders. No correlation between the deletion ranges and phenotypic variations was found. Conclusion: 16p11.2 deletions play causative roles in paroxysmal kinesigenic dyskinesia, especially for sporadic cases. Our findings extend the phenotype of 16p11.2 deletions to pure paroxysmal kinesigenic dyskinesia. Screening for 16p11.2 deletions should thus be included in genetic evaluations for patients with paroxysmal kinesigenic dyskinesia. Abstract : Out of 29 patients with paroxysmal kinesigenic dyskinesia with negative PRRT2 point and frameshift mutations, two patients were identified with 16p11.2 deletions. They were not complicated with intelligent disabilities. No correlation between the deletion ranges and phenotypic variations was found. Thus, 16p11.2 deletion should be included in routine genetic evaluations for patients with paroxysmal kinesigenic dyskinesia.